2018
DOI: 10.1007/s00109-018-1667-0
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34a targets sirtuin 1 and leads to diabetes-induced testicular apoptotic cell death

Abstract: MiR-34a mediates diabetes-induced TACD via inhibition of SIRT1. The novel SIRT1 activator SRT2104 attenuates diabetes-induced TACD. MiR-34a inhibition activates SIRT1 and prevents diabetes-induced TACD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…Moreover, oxidative stress, neuronal apoptosis, ischemic infarction, and neurological deficits were dramatically decreased in MCAO rats when an miR-34a inhibitor was used. These data indicated that miR-34a was involved in oxidative stress and neuronal apoptosis, which is consistent with previous studies [11,35,36].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, oxidative stress, neuronal apoptosis, ischemic infarction, and neurological deficits were dramatically decreased in MCAO rats when an miR-34a inhibitor was used. These data indicated that miR-34a was involved in oxidative stress and neuronal apoptosis, which is consistent with previous studies [11,35,36].…”
Section: Discussionsupporting
confidence: 93%
“…In 2018, scientists found that hippocampal neural apoptosis may arise as a consequence of high blood glucose in the streptozotocin-induced diabetic mice in response to increased acetylation of p53 and downregulation of SIRT1 [44]. Another report indicated that miR-34a targeted SIRT1 mRNA, which induced apoptosis in the testicular tissue of diabetes-induced C57BL/6 male mice [45]. In accordance with these findings, we noticed that the expression of miR-34a in the pancreas of diabetic rats was associated with the concomitant up-regulation of SIRT1 and P53, and acceleration of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of oxidative stress in the mouse testis results in an upregulation of miR-34a and downregulation of SIRT1. Upon oxidative stress, the testis displays higher expression of apoptotic markers and higher apoptotic index in male germ cells, indicating that oxidative stress is a major cause of male infertility ( 76 , 77 ). The members of the miR-34/449 family seems to exert significant anti-oxidant and anti-apoptotic properties and are vital for the testicular homeostatic mechanisms.…”
Section: The Role Of Mir-34/449 Family In Spermatogenesismentioning
confidence: 99%